Health Behavior among Female Carpet Weavers in Bandar Turkmen and Aqqala City, Iran, based on Health Belief Model (HBM) - Ali Zafarzadeh; Hashem Heshmati; Solmaz Barza; Rabie Arekhi; Abdoraman Charkazi (Golestan University of Medical Sciences, 2015)
Background and Objective: Carpet industry is the most important handicrafts in rural areas of Iran. Iranian carpet weavers are exposed to the risk of carpet weaving diseases and the side effects. This study aimed at assessing the health behavior of Bandar Turkmen and Aqqala carpet weavers based on the HBM, 2013. Material and Methods: This cross-sectional study was conducted on 200 female carpet weavers selected via census in Bandar Turkmen and Aqqala city, Golestan province. The data was collected by a Demographic checklist and HBM questionnaire and analyzed by using Pearson correlation coefficient, One-way ANOVA, post-hoc test and independent T test (;le0.05). Results: the mean age was 35.63±11.64 years. The perceived susceptibility was significantly correlated with perceived threat and perceived benefits (P<0. 001). Preventive behavior related to carpet weaving job diseases was insufficient among majority of the participants (78%). Conclusion: Given their high-perceived threat and perceived benefits regarding to diseases, carpet weavers less likely do preventive measures.  Further research is needed considering interpersonal and enabling factors.